Study of risk factors for infertility for Iraqi patients (a cross-sectional study of women aged 20-40 years). (Eurasian Medical Research Periodical, 2022)
This paper aims to assess risk factors for infertility for Iraqi patients through a crosssectional study of women aged 20-40 years. A specific questionnaire was applied to 120 Infertile women and 80 Normal women with aged between 25 and 50 years from September 2018 to September 2020 from several different hospitals. A questionnaire was designed by experts from the Infertility Technical Group of the Ministry of Public Health, and a database was created using Microsoft Access The result which found in this paper were (200 cases collected divided to 120 with Infertile women and 80 normal women) and the study revealed a high body mass index for women over the age of 40 years; 60 women were diagnosed with 50% of the patients' group 29-32 kg/m2.